2009
DOI: 10.1097/ta.0b013e3181b83b63
|View full text |Cite
|
Sign up to set email alerts
|

Computed Tomographic Angiography Versus Conventional Angiography for the Diagnosis of Blunt Cerebrovascular Injury in Trauma Patients

Abstract: Neither 16- nor 64-slice CT angiography is as accurate as CA as a screening tool for BCVI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
50
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 6 publications
0
50
0
Order By: Relevance
“…3,27,28 However DSA, the reference standard for BCVI detection, continues to be recommended despite being invasive, laborintensive, and available only in specialized centers. 3,4,9,25,[29][30][31] Most injuries missed on CTA are grade I injuries with luminal irregularity, but these have been shown to carry a significant risk of stroke. 3 In a meta-analysis comparing the accuracy of CTA against DSA for BCVI, Roberts et al 10 reported a pooled sensitivity of 66% and specificity of 97% for The incremental effectiveness in all iterations was negative (selective DSA has worse outcomes), and the incremental costs were positive (selective DSA is more expensive), suggesting that selective DSA is less cost-effective than selective CTA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,27,28 However DSA, the reference standard for BCVI detection, continues to be recommended despite being invasive, laborintensive, and available only in specialized centers. 3,4,9,25,[29][30][31] Most injuries missed on CTA are grade I injuries with luminal irregularity, but these have been shown to carry a significant risk of stroke. 3 In a meta-analysis comparing the accuracy of CTA against DSA for BCVI, Roberts et al 10 reported a pooled sensitivity of 66% and specificity of 97% for The incremental effectiveness in all iterations was negative (selective DSA has worse outcomes), and the incremental costs were positive (selective DSA is more expensive), suggesting that selective DSA is less cost-effective than selective CTA.…”
Section: Discussionmentioning
confidence: 99%
“…7 Digital subtraction angiography has been considered the reference standard for BCVI detection. 9,10 Increasingly, CT angiography is used in emergency departments to assess patients. 11 There is considerable variation in the reported sensitivity of CTA for BCVI detection in the literature, and its ability to replace DSA has not been validated, to our knowledge.…”
mentioning
confidence: 99%
“…The pattern of BCVI consists of vascular transection, dissection, thrombosis, and formation of pseudoaneurysm or arteriovenous fistula (AVF) 9,10 . The majority of these injuries occur during motor vehicle accidents, with variable rates of carotid and vertebral artery involvement reported in the literature [11][12][13] . If untreated, BCVI can be fatal and result in devastating neurological sequelae, with mortality and morbidity rates reported up to 38% and 67% respectively 14 .…”
mentioning
confidence: 99%
“…In their study the sensitivity, specificity, positive predictive value (PPV) and negative predictive value (NPV) of CTA were 97.7%, 100%, 100% and 99.3% respectively. In their prospective study of 158 patients Goodwin et al reported a lower sensitivity of 41% but a comparable specificity of 97% when combining both 16 and 64-slice CTA (10). In this study CTA was performed close to the time of injury whereas DSA occurred anywhere from 24-48 h post trauma.…”
Section: Computed Tomography Angiography (Cta)mentioning
confidence: 84%